TEKNIK YANG PALING DOMINAN PADA PERTANDINGAN FUTSAL PUTRI PROFESIONAL 2018 - Hanafi, Imam; Kusuma, I Dewa Made Aryananda Wijaya (Universitas Negeri Surabaya, 2021)
The results of this study aim to determine the technique that is often used or the most dominant used during professional women's futsal matches. This study uses quantitative research methods by watching matches through social media, namely YouTube. The sample used is purposive sampling. Data analysis used a frequency test of frequently used techniques. The results of this study indicate that the frequency of using passing techniques is 2064 times, control is 1879 times, dribbling is 254, feinting is 115 times, shooting is 243 times, heading is 36 times, turning is 42 times, and chipping is 44 times. Based on these results, it can be concluded that there are two techniques that are the most dominant or often used in professional women's futsal matches, namely passing and control techniques. From the results of this study, it has a positive impact for women's futsal coaches to be used as guidelines or references in undergoing an exercise program, especially on the most dominant technique carried out during matches.